Method for preparing antimony trioxide nanowire flexible integrated electrode by combining impregnation method and pyrolysis method
By using impregnation method and pyrolysis method on a flexible conductive substrate, the problem of volume expansion of the negative electrode material of lithium-ion battery during charging and discharging is solved, and efficient and low-cost flexible electrode preparation is achieved, and the cycle stability and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202510013514.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The volume expansion of antimony trioxide in the negative electrode material of the existing lithium-ion battery leads to capacity loss during charging and discharging. The traditional preparation method is costly and complicated, making it difficult to meet the needs of flexible batteries.
Using a combination of impregnation method and pyrolysis method, the antimony trioxide nanowire network structure is uniformly grown on the flexible conductive substrate to form a flexible integrated electrode. This method is simple to operate and low cost, which can effectively alleviate volume expansion and improve cycle stability.
It realizes efficient preparation of flexible integrated electrodes of antimony trioxide nanowires, improves the rate performance and cycle stability of electrode materials, reduces production costs, and is suitable for high capacity and long-life applications of flexible lithium-ion batteries.
Smart Images

Figure CN119812224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an antimony trioxide nanowire flexible integrated electrode. Background Art
[0002] With the development of flexible wearable devices, the demand for flexibility of their energy supply devices (i.e., batteries) continues to increase. Flexible lithium-ion batteries have excellent electrochemical energy storage capacity and mechanical stability, and play a vital role in flexible wearable devices. The actual specific capacity of graphite anodes that can be commercialized is close to the theoretical value (372 mAh / g), and the limited specific capacity cannot meet the market demand for high energy density batteries. Similarly, electrodes prepared by traditional coating slurries cannot meet the needs of flexible electronic devices. Therefore, seeking flexible lithium-ion battery anode materials with high theoretical specific capacity, high cycle stability and low production cost is crucial to promote the commercialization of flexible wearable devices.
[0003] At present, the materials that can be used for negative electrodes of lithium-ion batteries can be roughly divided into carbon materials, alloy materials, silicon-based materials, tin-based materials, antimony-based materials, etc. At present, antimony-based materials, such as antimony alloys, antimony oxides, and antimony sulfides, have attracted great attention as candidate negative electrode materials for lithium-ion batteries. Among them, antimony trioxide (Sb 2 O 3 ) stands out as an attractive negative electrode material due to its high theoretical capacity (1109mAh / g), low operating voltage, and good cycle stability.
[0004] However, Sb 2 O 3 There will be a large volume change during the charge and discharge process. The Li generated during the lithiation process 2 O will aggregate, affecting the first cycle coulombic efficiency and causing a large capacity loss. To solve this problem, many effective methods have been proposed, such as constructing microstructures or nanostructures, modifying them through unique synthesis methods, and compounding them with conductive carbon matrices. 2 O 3 Most electrodes need to be prepared by hydrothermal treatment or multiple high-temperature calcinations. The high preparation cost and complicated process make their large-scale application not optimistic, and most preparation methods cannot meet the needs of flexible batteries. Therefore, it is still urgent to develop a simple and cost-effective synthesis route for high-performance negative electrode materials for flexible lithium-ion batteries. Summary of the invention
[0005] In order to solve the above-mentioned problems of the prior art, the present invention provides a method for preparing a flexible integrated electrode of antimony trioxide nanowires by combining an impregnation method with a pyrolysis method; the synthesis method of the present invention is simple to operate, low in cost, and the preparation process is easy to control, which is beneficial to safe production and equipment protection; the present invention uniformly grows an antimony trioxide nanowire network structure on a flexible substrate to obtain a flexible electrode, which can effectively promote the ion / charge transfer of the electrode and greatly improve the rate performance of the electrode material; the lithium ion battery negative electrode material of the present invention can effectively alleviate the volume expansion effect of the material during the charging and discharging process, improve the lithium storage capacity and electronic conductivity, so that the flexible lithium ion battery can have a higher specific capacity and good cycle stability; the electrode of the present invention can be used as a negative electrode, especially as a flexible electrode, in high-capacity, long-life lithium ion batteries, especially flexible lithium ion batteries.
[0006] To achieve the above object, the present invention adopts the following technical solution.
[0007] The present invention provides a method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method with a pyrolysis method, comprising the following steps: a) immersing a clean flexible conductive substrate into an alcohol solution of a metal antimony salt and then taking it out, washing it and drying it; b) immersing the dried flexible conductive substrate obtained in step a) in an alcohol solution of ammonia to fully soak it, then taking it out, washing it and drying it; c) pyrolyzing the dried flexible conductive substrate obtained in step b) under inert gas protection to obtain a flexible integrated electrode with antimony trioxide uniformly grown on the substrate in a nanowire network structure.
[0008] In the present invention, in step a), the flexible conductive substrate is carbon cloth.
[0009] In the present invention, in step a), the concentration of the alcohol solution of the metal antimony salt is 0.2-2 mmol / mL; wherein the metal antimony salt is selected from one or more of antimony chloride, antimony acetate or antimony nitrate, and the alcohol solvent is selected from one or more of ethanol, propylene glycol or isopropanol.
[0010] In the present invention, in step b), the volume ratio of concentrated ammonia water to alcohol in the alcohol solution of ammonia water is 1:4-1:6; wherein the alcohol solvent is any one of ethanol, propylene glycol and isopropanol.
[0011] In the present invention, in step a), the soaking temperature is 0 to 40° C. and the soaking time is 2 to 7 days; in step b), the soaking temperature is 0 to 40° C. and the soaking time is 3 to 10 hours.
[0012] In the present invention, in step a) and step b), the conductive substrate is cleaned with an alcohol solvent, the main function of which is to wash away the unreacted substances on the surface of the flexible conductive substrate; the drying temperature is 40 to 80° C., and the drying time is 1 to 12 h.
[0013] In the present invention, in step c), the pyrolysis temperature is 250-400° C., the pyrolysis time is 2-4 h, and the inert gas is one or both of argon and nitrogen.
[0014] The present invention also provides a flexible integrated electrode of antimony trioxide nanowires prepared by the above method, wherein the flexible integrated electrode has a nanowire network structure; in a specific embodiment, the antimony trioxide nanowires are loaded on a flexible substrate, the diameter of the antimony trioxide nanowires is between 20 and 60 nm, the length is between 1 and 2.2 μm, and the nanowires are intertwined to form a uniform network structure.
[0015] Furthermore, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the antimony trioxide nanowire flexible integrated electrode is directly used as the negative electrode. Preferably, the lithium-ion battery is a flexible lithium-ion battery.
[0016] Compared with the prior art, the present invention has the following beneficial outstanding substantial features and significant advantages: 1. The present invention adopts a process combining impregnation and thermal decomposition to prepare a flexible antimony trioxide nanowire integrated electrode. The carbon cloth is used as the substrate to uniformly grow the antimony trioxide nanowire network structure. There are gaps between the antimony trioxide nanowires, which can effectively buffer the volume expansion of the material during the charge and discharge process and improve the cycle stability of the material; the carbon cloth substrate can fully promote the ion / charge transfer in the electrode and improve the rate performance of the electrode material. The prepared flexible integrated electrode does not require the use of non-electrochemically active substances such as binders, thereby improving the energy density of the battery.
[0017] 2. This method is simple to operate and has strong operability. The first two steps of the reaction can be carried out at room temperature or near room temperature, which greatly reduces energy consumption. No hydrothermal treatment is required to uniformly grow an antimony trioxide nanowire network structure on the surface of the carbon cloth, which will help to further expand production.
[0018] 3. The electrode material prepared by the present invention was tested, and the experimental results showed that the specific capacity was stably maintained at a level of not less than 986 mAh / g after 200 cycles of constant current charge and discharge at a current density of 1.0 A / g. The preparation method of the present invention is applied to the battery field, and flexible integrated electrodes can be prepared on a large scale, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Of course, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0020] Figure 1 This is the X-ray diffraction pattern of the negative electrode material prepared in Example 1.
[0021] Figure 2 This is a test diagram of the bending degree of the negative electrode material prepared in Example 1.
[0022] Figure 3 This is a scanning electron microscope photograph of a single carbon fiber loaded with antimony trioxide nanowires of the negative electrode material prepared in Example 1.
[0023] Figure 4 This is a scanning electron microscope photograph of antimony trioxide nanowires loaded on the surface of carbon cloth as the negative electrode material prepared in Example 1.
[0024] Figure 5 This is a transmission electron microscope photograph of antimony trioxide nanowires on the surface of the negative electrode material prepared in Example 1.
[0025] Figure 6 This is a rate performance diagram of the negative electrode material prepared in Example 1 when applied to a lithium-ion battery.
[0026] Figure 7 The charge and discharge cycle curve of the negative electrode material prepared in Example 1 when applied to a lithium ion battery at a current density of 0.1 A / g.
[0027] Figure 8 The charge-discharge cycle curve of the negative electrode material prepared in Example 1 when applied to a lithium-ion battery at a current density of 0.5 A / g.
[0028] Fig. 9 The charge-discharge cycle curve of the negative electrode material prepared in Example 1 when applied to a lithium-ion battery at a current density of 1.0 A / g. DETAILED DESCRIPTION
[0029] The negative electrode material prepared by the preparation technology adopted in the following embodiments of the present invention can effectively alleviate the volume expansion of the material during the charging and discharging process and improve the cycle stability of the material; the carbon cloth substrate can fully promote the ion / charge transfer in the electrode and improve the rate performance of the electrode material. The prepared flexible integrated electrode can reduce the use of non-electrochemically active substances such as binders and improve the energy density of the battery.
[0030] The present invention adopts a process combining an impregnation method and a thermal decomposition method as shown in the following embodiment, and can evenly grow an antimony trioxide nanowire network structure on the surface of a carbon cloth substrate. At the same time, the method is simple to operate and has strong operability. The temperatures required for the first two steps of the reaction are relatively low and can be carried out at ambient temperature, which greatly reduces energy consumption, and can be used to prepare flexible integrated electrodes on a large scale, which is suitable for industrial production.
[0031] The following embodiments of the present invention have no special restrictions on the counter electrode, diaphragm, battery shell, electrolyte, etc. The counter electrode can be a lithium sheet; the diaphragm can be a polypropylene (PP) microporous diaphragm; the electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). Specifically, the following embodiments of the present invention simply slice the flexible integrated electrode directly into a pole piece; the counter electrode is a lithium sheet, and 1 mol / L lithium hexafluorophosphate (LiFP) is used. 6 ) was used as the electrolyte, and a PP microporous separator was used to assemble a CR2016 simulated battery.
[0032] The following embodiments of the present invention conduct constant current charge and discharge experiments to test the cycle performance of the assembled lithium-ion battery, and the charge and discharge voltage is limited to 0.01 ~ 3 V. The CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. is used to test the electrochemical performance of the battery at room temperature.
[0033] To further illustrate the present invention, the following is a detailed description of a method for preparing a flexible integrated negative electrode of antimony trioxide nanowires by combining an impregnation method with a pyrolysis method, and the performance of a potassium ion battery with high capacity and long life, in combination with embodiments of the present invention. However, it should not be construed as limiting the scope of protection of the present invention.
[0034] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows.
[0035] Example 1
[0036] In this embodiment, a method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method and a pyrolysis method comprises the following steps: a) Dissolve 10 mmol of antimony trichloride in 20 mL of ethanol to prepare a 0.5 mol / L antimony trichloride ethanol solution. Immerse a clean carbon cloth in the solution. After soaking it at 20°C for 4 days, take it out, wash it with ethanol to remove the unreacted substances on the surface of the carbon cloth, and dry it at 60°C for 2 h.
[0037] b) The dried carbon cloth obtained in step a) is immersed in an ethanol solution of concentrated ammonia water and ethanol in a volume ratio of 1:5, and after soaking at 20° C. for 4 h, it is taken out, washed with ethanol to remove unreacted substances on the surface of the carbon cloth, and dried at 60° C. for 2 h.
[0038] c) heating the dried carbon cloth obtained in step b) to 300°C under nitrogen protection for 2 hours, and then cooling to room temperature to obtain a carbon cloth loaded with antimony trioxide nanowires, i.e., an antimony trioxide nanowire flexible integrated electrode; its XRD is as follows: Figure 1 As shown, the characteristic peaks correspond to the standard card JCPDS: 43-1071. The obtained integrated electrode was subjected to a bending test, as shown in FIG. Figure 2 As shown in the figure, the material has excellent flexibility and mechanical properties. Figure 3 , Figure 4 As shown in the figure, the antimony trioxide nanowires in the field of view present a uniform network structure, and the antimony trioxide nanowires are in close contact with the carbon cloth substrate, ensuring the structural stability of the flexible electrode material. Figure 5 As shown, it can be seen that the prepared antimony trioxide nanowires have a diameter of 20 to 60 nm, a length of 1 to 2.2 μm, and a uniform structure and size.
[0039] The rate performance of the prepared integrated electrode was characterized. When the current density gradually increased from 0.1 A / g to 0.2, 0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 A / g, the discharge specific capacity of the obtained integrated flexible electrode was 1459, 1278, 1126, 971, 779, 649, 562 and 471 mAh / g, respectively. When the current density returned to 0.1 A / g again, the discharge specific capacity also returned to 1303 mAh / g. The results are as follows Figure 6 As shown in Figure 2, the material exhibits good rate performance. The flexible integrated electrode was subjected to constant current charge and discharge tests at a current density of 0.1 A / g. The results are shown in Figure 2. Figure 7 As shown in the figure, after 100 cycles, the specific capacity remains at 1135 mAh / g, and the electrode exhibits high specific capacity and excellent cycle stability. At the same time, the constant current charge and discharge performance of the lithium ion battery of the present invention at a current density of 0.5 A / g was also tested. After 200 cycles, the specific capacity remained at 1008 mAh / g. The results are shown in the figure. Figure 8 The specific capacity of the lithium-ion battery in the present invention after 200 cycles of constant current charge and discharge at a current density of 1.0 A / g is not less than 986 mAh / g. Fig. 9 shown.
[0040] Example 2
[0041] In this embodiment, a method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method and a pyrolysis method comprises the following steps: a) Dissolve 15 mmol of antimony nitrate in 15 mL of propylene glycol to prepare a 1.0 mol / L antimony nitrate propylene glycol solution. Immerse a clean carbon cloth in the solution at 20°C for 3.5 days, then take it out, wash it with propylene glycol to remove the unreacted substances on the surface of the carbon cloth, and dry it at 60°C for 2 h.
[0042] b) The dried carbon cloth obtained in step a) is immersed in a solution of concentrated ammonia water and propylene glycol in a volume ratio of 1:5, and after soaking at 20° C. for 3 h, it is taken out, washed with ethanol to remove unreacted substances on the surface of the carbon cloth, and dried at 60° C. for 2 h.
[0043] c) The dried carbon cloth obtained in step b) is thermally decomposed at 350° C. for 2 h under nitrogen protection to obtain a flexible integrated electrode of antimony trioxide nanowires.
[0044] The microscopic morphology of the electrode material prepared in this embodiment presents a uniform network structure, and antimony trioxide nanowires grow uniformly on the carbon cloth substrate. The integrated electrode prepared in this embodiment was subjected to a bending test, and it was found that the material has good flexibility. The product prepared in this embodiment was subjected to a charge and discharge cycle test. After 200 cycles at a current density of 1.0 A / g, the capacity remained at 967 mAh / g, showing a high specific capacity and good cycle stability. The antimony trioxide nanowire carbon cloth prepared in this embodiment has excellent electrochemical properties and good mechanical properties, can meet the needs of flexible batteries and is suitable for large-scale industrial production.
[0045] Example 3
[0046] In this embodiment, a method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method and a pyrolysis method comprises the following steps: a) Dissolve 10 mmol of antimony nitrate in 25 mL of isopropanol to prepare a 0.4 mol / L antimony nitrate isopropanol solution. Immerse a clean carbon cloth in the solution at 25°C for 6 days, then take it out, wash it with isopropanol to remove the unreacted substances on the surface of the carbon cloth, and dry it at 60°C for 4 h.
[0047] b) The dried carbon cloth obtained in step a) is immersed in an isopropanol solution of concentrated ammonia water and isopropanol in a volume ratio of 1:4.5 at 25° C. for 5 h, then taken out, washed with isopropanol to remove unreacted substances on the surface of the carbon cloth, and dried at 55° C. for 4 h.
[0048] c) thermally decomposing the dried carbon cloth obtained in step b) at 380° C. for 3 h under nitrogen protection to obtain a flexible integrated electrode of antimony trioxide nanowires.
[0049] The microscopic morphology of the electrode material prepared in this embodiment presents a uniform network structure, and antimony trioxide nanowires grow uniformly on the carbon cloth substrate. The integrated electrode prepared in this embodiment was subjected to a bending test, and it was found that the material has good flexibility. The product prepared in this embodiment was subjected to a charge and discharge cycle test. After 200 cycles at a current density of 1.0 A / g, the capacity remained at 906 mAh / g, showing a high specific capacity and good cycle stability. The antimony trioxide nanowire carbon cloth prepared in this embodiment has excellent electrochemical properties and good mechanical properties, can meet the needs of flexible batteries and is suitable for large-scale industrial production.
[0050] Example 4
[0051] In this embodiment, a method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method and a pyrolysis method comprises the following steps: a) Dissolve 15 mmol of antimony acetate in 10 mL of butanediol to prepare a 1.5 mol / L antimony acetate butanediol solution. Immerse a clean carbon cloth in the solution and soak it at 35°C for 4.5 days. Then take it out, wash it with isopropanol to remove the unreacted substances on the surface of the carbon cloth, and dry it at 65°C for 2 h.
[0052] b) The dried carbon cloth obtained in step a) is immersed in an isopropanol solution of concentrated ammonia water and isopropanol in a volume ratio of 1:4.5, and after soaking at 35° C. for 3.5 h, it is taken out, washed with isopropanol to remove unreacted substances on the surface of the carbon cloth, and dried at 50° C. for 9 h.
[0053] c) The dried carbon cloth obtained in step b) is thermally decomposed at 280° C. for 4 h under nitrogen protection to obtain a flexible integrated electrode of antimony trioxide nanowires.
[0054] The microscopic morphology of the electrode material prepared in this embodiment presents a uniform network structure, and antimony trioxide nanowires are uniformly grown on the carbon cloth substrate. The integrated electrode prepared in this embodiment was subjected to a bending test, and it was found that the material has good flexibility. The product prepared in this embodiment was subjected to a charge and discharge cycle test. After 200 cycles at a current density of 1.0 A / g, the capacity remained at 989 mAh / g, showing a high specific capacity and good cycle stability. The antimony trioxide nanowire carbon cloth prepared in this embodiment has excellent electrochemical properties and good mechanical properties, can meet the needs of flexible batteries and is suitable for large-scale industrial production.
[0055] The above embodiment of the present invention provides a method for preparing a flexible integrated electrode of antimony trioxide nanowires by combining an impregnation method with a pyrolysis method, and its application in high-capacity and long-life lithium-ion battery performance. First, the carbon cloth is immersed in an alcohol solution of a metal antimony salt, such as an ethanol or propylene glycol solution of antimony trichloride or antimony nitrate, and then taken out, washed and dried; then the dried carbon cloth is immersed in an alcohol solution of ammonia water, such as ethanol, isopropanol, etc., and then taken out, washed and dried again; then the carbon cloth taken out, washed and dried after two immersions is heat-treated under protective atmosphere conditions, and thermally decomposed to obtain a flexible integrated electrode of antimony trioxide nanowires, and used for a flexible negative electrode of a lithium-ion electrode. The flexible antimony trioxide nanowire integrated electrode of the present invention uses carbon cloth as a substrate to uniformly grow an antimony trioxide nanowire network structure, and the gaps between the antimony trioxide nanowires can effectively alleviate the volume expansion of antimony trioxide during the insertion and extraction of lithium ions; the composite of antimony trioxide nanowires and a conductive substrate can effectively promote the ion / charge transfer of the electrode, greatly improving the rate performance of the electrode material. After 200 cycles of antimony trioxide nanowire integrated electrode at a high current of 1 A / g, the specific capacity remains at 986 mAh / g, showing excellent cycle stability and high specific capacity. Compared with the prior art, the first two steps of the method of the above embodiment of the present invention can be carried out at room temperature or near room temperature, with low energy consumption, low requirements for production equipment, and can be prepared in large quantities; the obtained antimony trioxide nanowire flexible integrated electrode has excellent electrochemical properties and flexibility, which can meet the needs of flexible batteries.
[0056] The above description is only an illustration of the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an antimony trioxide nanowire flexible integrated electrode by combining an impregnation method with a pyrolysis method, characterized in that: The following steps are involved: a) immersing a clean flexible conductive substrate into an alcohol solution of a metal antimony salt and then taking it out, washing it and drying it; b) immersing the dried flexible conductive substrate obtained in step a) in an alcohol solution of ammonia to fully soak it, then taking it out, washing it and drying it; c) pyrolyzing the dried flexible conductive substrate obtained in step b) under inert gas protection to obtain a flexible integrated electrode with antimony trioxide uniformly grown on the substrate in a nanowire network structure.
2. The method according to claim 1, characterized in that In step a), the flexible conductive substrate is carbon cloth.
3. The method according to claim 1, characterized in that In step a), the concentration of the alcohol solution of the metal antimony salt is 0.2-2 mmol / mL; wherein the metal antimony salt is selected from one or more of antimony chloride, antimony acetate or antimony nitrate, and the alcohol solvent is selected from one or more of ethanol, propylene glycol or isopropanol.
4. The method according to claim 1, characterized in that: In step b), in the alcohol solution of aqueous ammonia, the volume ratio of concentrated aqueous ammonia to alcohol is 1:4-1:6; wherein the alcohol solvent is any one of ethanol, propylene glycol and isopropanol.
5. The method according to claim 1, characterized in that In step a), the soaking temperature is 0 to 40° C. and the soaking time is 2 to 7 days; the soaking temperature is 0 to 40° C. and the soaking time is 3 to 10 hours.
6. The method according to claim 1, characterized in that In step a) and step b), the conductive substrate is cleaned with an alcohol solvent; the drying temperature is 40 to 80° C., and the drying time is 1 to 12 hours.
7. The method according to claim 1, characterized in that In step c), the pyrolysis temperature is 250-400° C., the pyrolysis time is 2-4 h, and the inert gas is one or both of argon and nitrogen.
8. A flexible integrated electrode of antimony trioxide nanowires prepared according to the method of any one of claims 1 to 7, characterized in that: The flexible integrated electrode has a nanowire network structure.
9. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The antimony trioxide nanowire flexible integrated electrode as claimed in claim 8 is used as the negative electrode.
10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery is a flexible lithium-ion battery.
Citation Information
Patent Citations
Preparation method of dumbbell-shaped negative electrode material for sodium-ion battery
CN105938922A
Preparation method of antimony oxide composite carbon cloth sodium ion battery anode material
CN106784663A
Preparation method of different valence state and crystal antimony oxide / carbon cloth flexible sodium ion battery negative electrode material
CN110277550A
Preparation method of antimony oxide / tin oxide composite nanowire
CN117228716A
Negative electrode active material for rechargable battery, method for manufacturing the same, and rechargable battery including the same
KR1020180022402A